The burden of surgical complications from unsafe abortion treated at the John F. Kennedy Maternity Center (JFKMC), Monrovia, Liberia - Odunvbun, Williams O.; Kollie, Jewel T. (Malawi medical journal, 2022)
Background The burden of surgical complications from unsafe abortion affects both health facilities and patients in most developing countries. This study aimed to determine the nature of surgical complications from unsafe abortion treated at the JFKMC, Liberia, and the estimated cost burden on facility and patient.MethodThis was a retrospective study of the medical records of patients who had exploratory laparotomy for complications of induced abortion and presented at the JFKMC from June 15, 2018, to December 15, 2019.ResultsThe medical records of 44 out of the 49 patients who had exploratory laparotomy for unsafe abortion were captured and analyzed. Surgical complications from unsafe abortion accounted for 17.8% out of the 276 gynaecological surgeries at the JFKMC, Liberia. The case fatality was 22.4%. The mean age of subjects was 29.00 ±6.06 years. About 1/3 of the subjects were in their teens, over 4/5 were single, and half were students. Almost 60.0% of the subjects terminated their pregnancies in private health facilities. Ten subjects had a hysterectomy for necrotic/septic uterus. The mean cost of managing a patient with surgical complications from unsafe abortion at the JFKMC was $331.50, in contrast with $22.00, for spontaneous or induced abortion with mild complications treated as a day case. ConclusionThis study showed a cost burden on the facility, and patients as a result of surgical complications from induced abortion. A shift in current practice by health facilities in Liberia to medical management of abortion and MVA, training of health personnel on the use of MVA, and a less restrictive abortion law with effective contraceptive services are recommended.